“Perversity, Futility, Jeopardy”: An Economic Analysis of the Attack on Gun Control - Cook, Philip J. (Law and contemporary problems, 1996)
A relatively new way for utilizing the thermal performance of heat pipes is to use nanofluids as working fluids in the heat pipes. Heat pipes are effective heat transfer devices in which the nanofluid operates in the two phases, evaporation and condensation. The heat pipe transfers the heat supplied in e.g. a laptop, from the evaporator to condenser part. Nanofluids are mixtures consisting of nanoparticles (e.g. nano-sized silver particles) and a base fluid (e.g. water). The aim of this bachelor’s thesis has been to examine the effect of nanofluids on heat pipes on the subject of temperature parameters and thermal resistance in the heat pies, through findings in literature and an applied model. The study, based on literature and an applied model, found that higher particle conductivity and higher concentration of nanoparticles consequently decrease the thermal resistance in the heat pipes, resulting in an enhanced thermal performance of the heat pipes with nanofluids as working fluids. It is however concluded that difficulties in finding the optimal synthesis of nanofluids, the concentration level of nanoparticles and the filling ratio of nanofluids in heat pipes, set bounds to the commercial use of nanofluids in heat pipes. It is suggested that, in order to enhance the heat transfer performance of nanofluids in heat pipes, to conduct further research concerning e.g. synthesis of nanofluids and concentration level of nanoparticles in nanofluids